2022
DOI: 10.24156/jikk.2022.15.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religiosity, Economic Pressure, Financial Management, and Stress Levels Towards Family Quality of Life During Covid-19 Pandemic in Indonesia

Abstract: An increasednumber of coronaviruscasesinfection has resultedininstability of household, which has animpact on family quality of life(QoL), and the facts during Covid-19 pandemic are contrary to the structural-functional theory, which emphasizes system stability and balance. This study aims to analyze the effect of religiosity, economic pressure, stress levels, and family management on family QoLduring the Covid-19 pandemic and to analyze family typology based on stress leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…Azzara, Simanjuntak, and Puspitawati (2022) investigated the influence of religiosity, economic pressure, financial management, and stress levels on family quality of life during the COVID-19 pandemic in Indonesia. They found that strong family bonds and effective financial management practices can mitigate the adverse effects of economic pressure (Azzara et al, 2022). This aligns with the findings of Morgan, Lim, and Washburn-Busk (2021), who explored financial stress and financial management roles within couples, revealing that open communication and shared financial responsibilities can reduce financial disagreements and stress (Morgan et al, 2021).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Azzara, Simanjuntak, and Puspitawati (2022) investigated the influence of religiosity, economic pressure, financial management, and stress levels on family quality of life during the COVID-19 pandemic in Indonesia. They found that strong family bonds and effective financial management practices can mitigate the adverse effects of economic pressure (Azzara et al, 2022). This aligns with the findings of Morgan, Lim, and Washburn-Busk (2021), who explored financial stress and financial management roles within couples, revealing that open communication and shared financial responsibilities can reduce financial disagreements and stress (Morgan et al, 2021).…”
Section: Introductionsupporting
confidence: 62%
“…The COVID-19 pandemic has exacerbated economic hardships for many families, highlighting the need for effective coping strategies and support systems. Azzara, Simanjuntak, and Puspitawati (2022) found that families with strong religiosity and effective financial management practices were better able to maintain their quality of life E E-ISSN: 3041-8550 during the pandemic (Azzara et al, 2022). Lee et al (2022) investigated the pathways from economic hardship to couple conflict during COVID-19 in Korea, finding that socioeconomic status played a significant role in moderating these effects (Lee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Temuan penelitian tersebut sejalan dengan berbagai hasil penelitian sebelumnya, yakni semakin tinggi stres yang dirasakan orang tua maka kemampuan melakukan pengasuhan akan semakin rendah (Donker et al, 2021;Gulliford et al, 2015;Riany & Ihsana, 2021). Menurut Azzara et al (2022), semakin besar stres orang tua akan semakin memperburuk kualitas hidup keluarga. Ibu yang mengalami stres cenderung tidak dapat mengontrol dirinya dengan baik.…”
Section: Pengaruh Karakteristik Anak Karakteristik Keluarga Dan Manaj...unclassified
“…Individuals who are economically depressed and do not have sufficient resources to deal with these pressures will tend to increase the crisis in themselves and their families. Research by Azzara et al (2022) stated that the impact of the Covid-19 pandemic has increased economic pressure on most individuals as measured by the difficulty in meeting basic needs and a drastic decrease in income which has an impact on reducing the quality of life. In addition, Raharjo et al (2015) found that economic pressure can increase conflict and feelings of depression and minimize family welfare and quality of life.…”
Section: Locus Of Control and Debt Behaviormentioning
confidence: 99%